Near infrared spectroscopy: a potential method to detect undifferentiated bovine respiratory disease - Fox, Jeffrie Thomas (Kansas State University, 2008)
Two studies were undertaken to evaluate the use of Near Infrared Spectroscopy (NIRS) to determine arterial oxygen saturation (StO[subscript]2) in cattle with naturally-occurring Undifferentiated Bovine Respiratory Disease (UBRD) and experimentally-induced UBRD utilizing Mannheimia haemolytica. The first study was a natural infection model utilizing 679 beef heifers weighing approximately 227 kg (500 pounds) originating from a southeastern U.S. salebarn. Heifers were evaluated for UBRD upon feedlot arrival, at revaccination, at day 35 on feed, at re-implant time, and two weeks prior to shipment for slaughter. Animals deemed to have UBRD were treated for UBRD and data was collected for 5 days following treatment, while a comparable healthy cohort was also evaluated at the time of treatment. There was a trend for NIRS to be able to predict the incidence of subsequent UBRD when cattle were evaluated on arrival (p=0.0552). However, the ability to detect UBRD in clinically ill cattle was not significantly different (p>0.1690) when compared to healthy cohorts in this model. When carcass characteristics were evaluated at each time point, NIRS StO[subscript]2 values were able to differentiate between yield grades of animals with UBRD and healthy cohorts when evaluated at revaccination, day 35, re-implant, and pre-shipping (p<0.0199). NIRS tended to be able to differentiate yield grades at initial processing (p=0.0513). StO[subscript]2 was not a predictor of quality grade at any time point (p>0.1023), nor was there any correlation between lung lesions at slaughter and StO[subscript]2 (p>0.2292). The second study involved 12 head of 181 kg (400 pound) heifers which were subjected to an experimental challenge model of Mannheimia haemolytica. Animals were evaluated daily and StO[subscript]2 readings recorded 12 hours pre-inoculation, at inoculation, 6, 12 and 24 hours post inoculation and daily for the next 12 days. While NIRS could not definitively differentiate healthy cohort cattle from challenge cattle (p>0.0713), there were trends toward challenge cattle having lower StO[subscript]2 values than healthy controls. The authors conclude that while these studies did not provide conclusive evidence of the ability of NIRS to detect UBRD, further studies with a machine that is specifically calibrated and designed for use with cattle should be performed.
Keywords: Near Infrared Spectroscopy; Bovine Respiratory Disease; Cattle; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Animal Pathology (0476)